Clinical efficacy of chitosan‐based hydrocolloid dressing in the treatment of chronic refractory wounds. Issue 8 (7th May 2022) - Liu, Jing; Shen, Hong
Abstract: This retrospective study aimed to explore the clinical efficacy of chitosan‐based hydrocolloid dressing in treating chronic refractory wounds. A total of 80 patients with chronic refractory wounds were randomly divided into the control group (n = 40) and the study group (n = 40). The control group was given inert saline gauze, while the study group was given chitosan‐based hydrocolloid dressing. After 3 weeks of treatment, the wound healing efficiency, itching pain score, changes in the wound area, dressing change frequency, and cost were measured. There was a significant difference in the wound healing effect (t = 2.738), and degree of pain (t = 4.76) between the study and control groups, after 3 weeks of treatment. Similarly, a prominent reduction in the itching frequency (t = 8.62), and wound area (t = 6.379) was observed in the study group compared to the control group ( P < .05). Moreover, the frequency and total cost of dressing change in the study group were also lower than the control group and the difference was statistically significant ( P < .05). To summarise, the application of chitosan‐based hydrocolloid dressing in treating chronic refractory can effectively alleviate pain, accelerate wound healing, relieve itching pain, and reduce the overall cost and frequency of dressing change.